Fiqh Review of Types of Fasting and Their Conditions - Aisy, Salwatul (Maliki Interdisciplinary Journal, 2025)
This article discusses the various types of fasting in Islam according to fiqh, including obligatory, sunnah, makruh, and haram fasting and their provisions. In Islam, fasting is not only understood as restraining hunger and thirst, but as a form of worship that has spiritual, moral, social and educational dimensions. Each type of fasting has different laws, times, and wisdom that must be understood by every Muslim so that its implementation is valid and meaningful. This research emphasizes the importance of understanding the conditions, pillars, and things that invalidate or disgrace fasting so that Muslims can carry it out correctly according to sharia guidance. Through a descriptive qualitative approach with a literature study, this article aims to provide education and understanding to the public about how fasting becomes an instrument of character building, self-control, and increasing piety to Allah SWT.